Effectiveness of Virtual Reality Distraction in Reducing Pain, Fear, and Anxiety Among Children Undergoing Invasive Procedures: A Systematic Review - farid_talango; Cahyaningtyas, Anindhita Yudha (Jurnal Stethoscope, 2025)
Invasive medical procedures such as venipuncture often cause pain, fear, and anxiety in children. Virtual Reality (VR) is an immersive technology that is increasingly used as a non-pharmacological distraction tool to reduce such discomfort. This study is a systematic review conducted following the PRISMA guidelines. Literature searches were performed across Google Scholar, ProQuest, PubMed, ScienceDirect, and SpringerLink using the keywords: "virtual reality" OR "VR" AND "pain" OR "fear" OR "anxiety" AND "children" OR "pediatric" AND "invasive procedures" OR "medical procedures", limited to articles published between 2022 and 2025. From a total of 294 articles, 7 were selected after a thorough screening process. The use of VR significantly reduced pain, fear, and anxiety scores compared to conventional methods. Its effectiveness was more prominent among school-aged children with higher cognitive abilities and familiarity with digital devices. Virtual Reality is proven to be an effective distraction tool in reducing pain, fear, and anxiety in children undergoing invasive medical procedures and should be considered as a standard intervention in pediatric healthcare settings.